2004
DOI: 10.1007/s10350-004-0525-z
|View full text |Cite
|
Sign up to set email alerts
|

Delay of the First Onset of Pouchitis by Oral Intake of the Probiotic Strain Lactobacillus rhamnosus GG

Abstract: Daily intake of fermented products containing L. rhamnosus GG provides significant clinical benefit, without side effects. Based on the results of this study, we recommend a daily intake of Lactobacillus rhamnosus GG (dose 1-2 x 10(10) bacteria) to delay the first onset of pouchitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(76 citation statements)
references
References 51 publications
0
72
1
3
Order By: Relevance
“…A specific probiotic has been found to modulate the expression of genes involved in cell growth and differentiation in the intestinal mucosa of human volunteers [27] . Probiotics have also been successfully applied in patients with IBD [28,29] or diverticulitis [30] . Several studies indicate that aberrancies in faecal microbiota are present in different diseases, and our results strengthen those studies with colonic mucosa data.…”
Section: Discussionmentioning
confidence: 99%
“…A specific probiotic has been found to modulate the expression of genes involved in cell growth and differentiation in the intestinal mucosa of human volunteers [27] . Probiotics have also been successfully applied in patients with IBD [28,29] or diverticulitis [30] . Several studies indicate that aberrancies in faecal microbiota are present in different diseases, and our results strengthen those studies with colonic mucosa data.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of probiotic treatment for inflammatory bowel disease, however, have yielded conflicting results. Some of them have confirmed the claim that a daily intake of probiotics will delay the first onset of pouchitis and that they are effective in the treatment of active Crohn's disease [10,11] while others failed to a show a beneficial affect [12] .…”
mentioning
confidence: 72%
“…From etiological and pathogenetic perspectives, a variety of factors may contribute to the initiation, development, and progression of the disease. These factors include genetic predisposition, 20,21 dysbiosis, 1-4 altered mucosal immunity, [22][23][24][25][26][27][28] and colonic metaplasia due to fecal stasis, 29,30 A previous study demonstrated that a decreased intramucosal pH with mucosal acidosis characteristic of hypoperfusion was associated with an increased risk for the development of pouchitis. 15 The findings of the current study suggest that pouchitis with endoscopic asymmetric inflammation may be associated with ischemic factors.…”
Section: Discussionmentioning
confidence: 97%